(Neo-)Bogomil Legends: The Gnosticizing Bogomils of the Twentieth-Century Balkans - Burns, Dylan; Radulović, Nemanja (International Journal for the Study of New Religions, 2018)
This contribution examines two modern, "Neo-Bogomil" groups: the Universal White Brotherhood (Bulgaria), and the Balkan Bogomil Center (Croatia). Both of these groups claim not only the authority of Bogomilism but ancient "Gnosticism," articulating these dualist heresies in terms of Theosophy as well as South-Eastern European religious and ethnic-national identities formulated in the later nineteenth century.